Perception et gestion des variations environnementales : le cas de la société insulaire oléronnaise (France) - David Chionne (Bulletin de l’Association de Géographes Français)
This article is part of our thesis, whose research central topic is the “risk culture” of Oleron Island’ society in regard to the coastal hazards of flooding and beach erosion. We reflect on the relations between society and environmental change, using a preliminary analysis of the results from a survey of the ways residents of Oleron perceive and react to coastal hazards. Specifically, we question the significance of a result in our first analysis of a sample of 268 individual answers: 2 people out of 5 cited “climate change” when asked to identify the causes of coastal hazards. This number led us to explore these questions: what knowledge do people have of “climate change” and changes in their environment? what does this imply in terms of behavior? is there a connection between knowledge and behavior?